Optimizing the Management of Gampong-Owned Enterprises (BUMDes) - Faisal, Faisal; Zuhra, Syarifah Evi; Murkhana, Murkhana; Adam, Muhammad; Mahdani, Mahdani; Musnadi, Said; Kesuma, T. Meldi; Siregar, M. Ridha; Humaira, Radhia; Syahrizal, Teuku Muhammad (Jurnal Pengabdian Bakti Akademisi, 2024)
This service activity is carried out to provide education related to optimizing management of Village/Gampong-Owned Enterprises which aims to improve the village economy by increasing community efforts in managing the village's economic potential. The aim of this service program is to assist the community in optimizing Village-Owned Enterprises (BUMDes) by strengthening BUMDes management capabilities so that they can be run sustainably and professionally. This is done by providing assistance and training to BUMDes administrators and members in terms of business management, finance, marketing and entrepreneurship as well as in aspects of compliance with statutory regulations in managing village potential. The events carried out in this activity are in the form of workshops with education related to the material needed in managing BUMDes as well as other events that can provide education and also help the community achieve the maximum village economy.